(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2025)
This research aims to reflect on the use of makeup in the process of characterization of characters, from the point of view of a “makeup-artist”, who observes it as a “multiple skin” of the actor, which multiplies and (in)corporates in various means and scenic elements. Thus, we will understand it beyond its technical function as a visual language, a beautification effect, or a mere element of character delineation. In doing so, we will trace the process of constructing this skin across diverse media and techniques, examining the factors and elements of a complex creative network, whether that process is material (physical plane) or virtual (mental plane).